Jurnal Spiritual Reflektif sebagai Media Pedagogis untuk Memperkuat Moderasi Beragama dalam Pendidikan Dasar Multikultural - Dwi Nisrina Khumairoh; Nuita Alifia Hasanah; Mahin Anas Romadona (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2026)
Religious, cultural, and social diversity in elementary education requires pedagogical strategies that move beyond cognitive understandings of tolerance toward reflective and sustained value internalization. This study describes the implementation of spiritual journals as reflective media for strengthening multicultural values and religious moderation among elementary school students. Using a qualitative case-study design at SD Bruderan Purwokerto, data were collected through observation, interviews, and documentation involving the principal, teachers, and students, and analyzed through data condensation, data display, and conclusion drawing. The findings show that spiritual journals provide students with space to write, interpret, and reflect on religious experiences according to their beliefs. This practice encourages regular spiritual engagement while connecting religious experience with tolerance, empathy, respect for difference, and peaceful coexistence. The study affirms spiritual journals as relevant pedagogical-reflective media for fostering inclusive, tolerant, and moderate religious attitudes in plural elementary-school contexts